UTILIZATION OF E-COMMERCE FOR MSMEs, COMMUNITIES, AND GOVERNMENT DURING THE COVID-19 PANDEMIC - Jam'an, Jam'an (KOMITMEN: Jurnal Ilmiah Manajemen, 2020)
The impact of the COVID-19 pandemic on Indonesia and the rest of the world is enormous. One of the affected parties is Micro, Small, and Medium Enterprises (MSMEs), so the people's economy in this business is significantly threatened. Therefore, there needs to be an effort to improve the Indonesian people's economic condition, especially MSME business players. One of the steps that can be taken to solve this problem is to use e-commerce. This research will be carried out using a qualitative approach. The study results found that three factors can be used to take advantage of e-commerce, namely organizational characteristics, environmental characteristics, and leadership characteristics. In addition, this study also found the benefits of using e-commerce for MSME actors, the community in general, and the government.